Non-invasive imaging of intracellular mRNA dynamics using molecular beacon-based nanosensors - Chew, Sharon Wan Ting (2016)
Messenger RNA is a key player in the regulation of cellular activities. Real-time assessment of intracellular mRNA dynamics can offer invaluable insights into the inner workings of cells. Previous imaging techniques suffer from the inefficient delivery of imaging probes into cells and false positive signals due to endonuclease digestion. In this paper, we introduce a novel approach to allow both the control of mRNA expression as well as non-invasive imaging of intracellular mRNA dynamics during gene activation period by incorporating the molecular beacon-based nanosensors into regulated gene expression system – Tet-On system. The molecular beacon-based nanosensors were synthesized by encapsulating mRNA-specific molecular beacons into PLGA nanoparticles. Using Enhanced Green Fluorescence Protein (EGFP) as a case study, the conditions were optimized to ensure efficient nanosensor uptake and optimal EGFP Tet-On system activation. With the activation trend of Tet-On system established, the kinetics of the nanosensors was examined during the gene activation period (0 – 48 hours). The nanosensors exhibited high specificity towards EGFP mRNA and do not interfere with EGFP gene expression. Most importantly, the nanosensors have high specificity and sensitivity towards EGFP mRNA comparable to that of reverse transcription quantitative polymerase chain reaction (RT-PCR).